Quantum Mechanical Calculations of R-O Thermal Bond Rupture Energies in Some Ampicillin Prodrugs - Kubba, Rehab; Abdul Sallam, Ali (Iraqi Journal of Science, 2024)
PM3 and Unrestricted Hartree Fock (UHF) quantum mechanical methods are carried out for the estimation of reaction path for the breakage of (R-O) bond rupture energies, for twelve ampicillin ester prodrugs derivatives, at their calculated equilibrium geometries, in addition to some physical properties such as heat of formation, total energy, dipole moment and the energy difference of EHOMO and ELUMO (ΔEHOMO-LUMO) energy levels, using the Gaussian-03 program. Comparisons were done between the total energies of the reactants, products, activation energies and transition states. The results show non possible use of some substituted organic groups as a carrier linkage for acidic ampicillin drug, whereas others show possible use as a carrier linkage. Density functional theory (DFT) calculations at a B3LYP/6-311G level were carried out for assignment IR vibration frequencies of R-O bond and for some important modes, for all ampicillin derivatives, depending on the pictures of its modes obtained from calculated IR spectra.